Effects of Thermal Stress on Behavioural Patterns of Legally Protected Indian Soft-shell Turtle Lissemys punctata - Basu, Pounami; Basu, Prajna Paramita (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Lissemys punctata, the Indian fresh-water soft-shelled turtle is a species under threat which has been classified as a Schedule-I animal under Wildlife Protection Act 1972 and in CITES is marked as ‘Vulnerable’. A high demand for its’ meat being rich in protein and considered to be a delicacy results in its illegal sale in international and local markets till date though it is prohibited by law. The study aims to investigate the effects of high temperature on the physiology of freshwater turtle, L. punctata and to observe their coping abilities with respect to wide fluctuations of environmental temperature. In the present study, adult soft-shelled turtles were rescued, collected from local market of Doltala in North 24 Parganas, West Bengal and kept in the garden with diverse plant and grass varieties and an adjacent water body. An artificial culture conditions were created in the garden with different soil types and the turtles were fed with food and water ad libitum. Our method is based on the principle- ‘study of ecology of turtle in captivity’. In this study feeding, breeding and nesting behaviour including habitat preference of Lissemys punctata from the month of February 2023 to May 2024 were observed. Behavioural changes and reduction in food intake were observed which shows adaptability to thermal stress by regulating Corticosterone Releasing Factor and Adrenocorticotrophic Hormone (CRF-ACTH) axis. The study emphasizes the significance of freshwater turtles as vital part of food web and ecosystem while identifying key threats including environmental fluctuations, effects of pollution and human activities and proposes necessary conservation strategies. Existing laws and regulations are reviewed to devise appropriate methods for protection of freshwater turtles and argues that most efforts have focussed on protection of sea-turtles which need to be replicated for freshwater turtles through use of different methods like Captive Husbandry, promotion of Citizen Science, usage of genetic markers (mitochondrial markers) and advanced technology.